To apply the property of negative integer exponents, we can use the fact that \( a^{-n} = \frac{1}{a^n} \) to convert the exponents into positive ones.
Starting with the expression:
\[ 7^{-3} \cdot 7^{-5} \]
We can combine the terms using the property of exponents \( a^m \cdot a^n = a^{m+n} \):
\[ 7^{-3} \cdot 7^{-5} = 7^{-3 + (-5)} = 7^{-8} \]
Now, we can convert the negative exponent to a positive exponent:
\[ 7^{-8} = \frac{1}{7^8} \]
So the expression \( 7^{-3} \cdot 7^{-5} \) with positive exponents only is:
\[ \frac{1}{7^8} \]